Promoting Algerian tax reform through reform and modernization of tax administration - بوقلع, وداد; حراق, مصباح (Finance and Business Economies Review, 2021)
This research paper attempted to highlight the mechanisms of promoting tax reform in Algeria, By focusing on the reform and modernization of the tax administration with the goal of adapting and making it more responsive to the contemporary challenges posed by the global environment today, as a result of the ongoing changes and developments, as well as Algeria's economic conditions. The study concluded that despite Algeria's efforts to enhance the efficiency and effectiveness of its tax administration at the level of its structures, resources, procedures, services and its relations with the tax community, it is still weak and insufficient, requiring political will and concerted efforts to ensure successful tax administration reform and modernization by focusing on digitization, facilitating procedures and improving her relationship with taxpayers.